THE MODERATING ROLE OF LOYALTY ON FINANCIAL PERFORMANCE OF LOGISTICS SOES - Hutama, Dusty Widha; Kholmi, Masiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effects of accountability, service quality, and asset management on the organizational performance of logistics SOEs, with employee loyalty serving as a moderating variable. The population of this study comprises all employees of logistics sector SOEs in Indonesia. A purposive sampling technique was employed, resulting in 133 valid responses collected from various logistics SOEs, which met the minimum requirements for statistical analysis. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze both direct relationships and moderating effects within the proposed research model. The results indicate that accountability has a positive and significant effect on organizational performance, while asset management and service quality do not have a direct effect on organizational performance. However, employee loyalty significantly moderates the relationships between asset management and organizational performance as well as between service quality and organizational performance. Employee loyalty functions as a pure moderator, indicating that asset management and service quality contribute to organizational performance only when supported by high levels of employee loyalty.